Study of the influence of mass media on the formation of suicidal thoughts among adolescents - Baymukhambetova, Botagoz; Ogiyenko, N.; Ibrayeva, Rakhima; Nurmagambetova, Lyaylya; Kovsh, Natal’ya; Shilov, Igor (Anais da Academia Brasileira de Ciencias, 2017)
The article highlights the results of an online survey of adolescents on the study of the mass media influence on the formation of suicidal thoughts and the analysis of sites devoted to the topic of suicides. It was revealed that the majority of adolescents are active users of the Internet and adolescents often face information about suicide in social networks, on information sites. The study also showed that the formation of suicidal behavior in adolescents is most affected by the dominance of cruelty and crime on television, leading to the introduction in the minds of adolescents of the notion of "everyday" violence and death, including murder and suicide; Also computer games aimed at the formation of cruelty, frivolous, or romantic attitude towards death in adolescents. Content analysis of sites devoted to the subject of suicide testifies that on the Internet it is possible to freely find whole sites and groups with detailed descriptions of the methods of suicide without any restrictions that push teenagers to the last point, and detailed stories of suicides cause the desire to imitate the other teenagers. Based on the results of the study, the article presents a number of recommendations on the specifics of media coverage of information about suicides.
Keywords: suicidal behavior; suicidal thoughts; adolescence; suicide; mass media; Internet